PANGGILAN DAN PELAYANAN DALAM KONTEKS BERGEREJA DI HKBP - Ance Marintan D. Sitohang (Institut Agama Kristen Negeri (IAKN) Ambon, 2018)
Call and service are divine mandate carried out by humans for the glory of His name. God calls to reveal His will to humans. Serving as a call means that we respond to God's salvation work in our lives by being partners with God, doing divine tasks and doing care for His church until the Lord Jesus returns. God calls generally to all people to believe in Him, but on the other hand, God also calls certain people whom He wants for the assignments He will give. In the context of Churching in HKBP, this particular call is stated through the call of the servant of the sanctifying ceremony (Partohonan). There are six ordination services in HKBP, namely: Presbyter, Church Teachers, Pastors, Evangelists, Biblevrow, and Deaconesses and each office of ordination ministers in HKBP have its own characteristics and duties.Keywords: call, service, HKBP Church